Christ, Power and Mammon : Karl Barth and John Howard Yoder in Dialogue. - Prather, Scott (London : Bloomsbury Publishing, 2013)
Thisbook examines the role of the New Testament concept of the 'principalities andpowers' in the thought of Karl Barth and John Howard Yoder, showing how thisbiblical concept of power is central to the fundamental theological convictionsof each thinker. Prather offers a scholarly account of the underexploredtheological and ethical import of a major biblical theme and the book addressesquestions and concerns from a wide range of academic and lay theologicalinterest. He brings Barth and Yoder into dialogue here and examines the threecrucial areas: the 'confessional' distinction of church and wor.
5 Naming and ResistanceI. Ellul and Stringfellow on money as Mammon; A. Jacques Ellul: Mammon as money; B. Stringfellow on the social corruption of Mammon; II. Faith beyond ideology? Barth, socialism and the vulnerability of resistance; A. The problem, restated; B. The theo-logic of Barth's 'socialist speeches'; III. Final remarks: Katrina and disaster/capitalism; Notes; Bibliography; Index of Names and Subjects; Index of Scripture References.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Barth, Karl, -- 1886-1968.; Yoder, John Howard; Jesus Christ -- Person and offices; Barth, Karl, -- 1886-1968; Jesus Christ; Yoder, John Howard; Power (Christian theology) -- Biblical teaching; Power (Christian theology) -- History of doctrines -- 20th century; Powers (Christian theology) -- Biblical teaching; Powers (Christian theology) -- History of doctrines -- 20th century; Wealth -- Religious aspects -- Christianity; Pouvoir (Théologie chrétienne) -- Enseignement biblique; Pouvoir (Théologie chrétienne) -- Histoire des doctrines -- 20e siècle.; Puissances (Théologie chrétienne) -- Enseignement biblique; Puissances (Théologie chrétienne) -- Histoire des doctrines -- 20e siècle.; Richesse -- Aspect religieux -- Christianisme; RELIGION -- Christian Theology -- Angelology & Demonology; Christology; Power (Christian theology) -- Biblical teaching; Power (Christian theology) -- History of doctrines; Powers (Christian theology) -- Biblical teaching; Wealth -- Religious aspects -- Christianity; 1900-1999